Properties of fibre bragg grating in optical fibre systems - Ikhsan, Sabirin; Muhamad Supian, Hairurizal; Abdul Rahman, Rosly (2000)
A fibre Bragg grating is a short section of optical fibre in which the core refractive index has a periodic modulation. They are produced by exposing a photosensitive fibre to a periodic pattern of ultraviolet (UV) light. Their fundamental property is to reflect light over a narrow spectral range centered at a resonant wavelength known as the Bragg wavelength. Their ease of fabrication, combined with their unique properties, make them ideal for a great number of applications in telecommunication and sensing. A study of the Bragg grating properties is discussed in this paper. This study concentrates on the wavelength shift, reflectivity and bandwidth or FWHM of Bragg gratings.